PKM Penyuluhan Peningkatan Keterampilan Kader Posyandu dan KWT Anggrek Desa Bencah Dalam Era New Normal - Fransiskus Panca Juniawan; Kgs. Muhammad Faizal; Dwi Yuny Sylfania; Nurhayati Nurhayati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Bencah Village has a history of being a village that has a high Covid-19 positive confirmation rate in Bangka Belitung Province. To prevent this incident happening again, the role of the Bencah Village Cadre must be increased. Bencah Village currently has Posyandu Cadres and KWT Anggrek Cadre who are active in serving public health. For this reason, counseling for cadres is needed as a form of support and guidance by skilled health workers. This Community Partnership Program activity aims to provide counseling about Covid-19 and Posyandu that must be mastered by cadres in this new normal era. The activity stages consist of the stage of Pre-Activity, Preparation, Implementation, and Evaluation. A total of 17 cadres participated in this activity, and at the end of the activity, all participants were asked to fill out a questionnaire survey to find out the results and impacts of the activities that have been carried out. From the results of the questionnaire analysis obtained an average value of 4.29 which means the activities have been carried out well.